Protocolo de avaliação rápida de indicadores de erosão em taludes fluviais: subsídios para aplicação do método Monteiro - Schettert, Teiva Fernanda (2015)
The development of rapid assessment protocols that work with indicators of erosion brittleness of river embankments, aims to relate parameters and provide diagnostics to assist in the management of water resources. Providing a new tool to be explored, with great possibility to be adopted as a method of practice and to generate reliable results. This research deals with the study of the Rapid Assessment Protocol (RAP) derived from the doctoral thesis "Indicators Brittleness Erosion in support of definition of Permanent Preservation Areas in rivers" of Josita Soares Monteiro, presented in 2014. The RAP consists of admittedly influential parameters on the stability of river embankments - vegetation; soil texture; stretch of the river; slope inclination; soil depth in slope; width of the stream and use and land cover - and of weights / notes concerning the characteristics of these parameters. As a result, the protocol provides a gradual classification concerning the state of "susceptibility to erosion" of the banks of the stream of Val Buia in Silveira Martins/RS, where this research was conducted. Amplification of the weight assigned to the parameters that make up the RAP of Monteiro (2014); performing a sensitivity analysis on RAP parameters in order to identify those that provide greater relevance in its final outcome; the implementation of changes in the criteria and structure of RAP and its reuse in the thesis study area, the stream Val Buia; and comparing the results of the original PAR with the PAR reapplied were the objectives of the study. The increase made on the weights of RAP parameters did not change the result of the classification of the sampling units in the categories of susceptibility to erosion. Sensitivity analysis demonstrated that the most sensitive parameters to changes in their weights are the highest scored, and, consequently, features which provide high susceptibility to erosion of the river embankments. The protocol used in the study area had partially similar result to that of Monteiro (2014). In order to better target the interpretations regarding the description of the area observed during visual assessment, it is suggested the preparation of well-defined characterization and typologies of measures for the RAP parameters evaluated. The addition of a new parameter in the protocol of Monteiro (2014) - the "river longitudinal profile" parameter - could provide better assessment of the areas that are affected by successive floods. Several fronts related to the assessment of the physical and environmental conditions of river embankments, such as environmental zoning, recovery projects of degraded areas and recovery of riparian forests may make use of the methodology proposed by RAP, as well as adding subsidies to the formulation and execution of natural engineering works aimed at stabilizing the banks of waterways.